Shallow tillage mitigates plant competition by increasing diversity and altering plant community assembly process - Li, Zihao; Qiao, Jirong; Li, Zhuofan; Gao, Xiaowei; Hong, Guangyu; Yang, Haifeng; Hu, Ercha; Liu, Chenming; Wang, Xiaojiang; Liu, Guanzhi; Gao, Runhong (Frontiers in Plant Science, 2024)
Understanding how human activities affect biodiversity is needed to inform systemic policies and targets for achieving sustainable development goals. Shallow tillage to remove Artemisia ordosica is commonly conducted in the Mu Us Desert. However, the impacts of shallow tillage on plant community species diversity, phylogenetic structure, and community assembly processes remain poorly understood. This study therefore explores the effects of shallow tillage on species diversity including three α-diversity and two β-diversity indicators, as well as phylogenetic structure (phylogenetic diversity [PD], NRI and NTI). Additionally, this research analyzes the effects of shallow tillage on the community assembly process. The results showed that the α-diversity index, β-diversity index, and PD of the shallow tillage (ST) communities were significantly higher than those of the nonshallow tillage (NT) communities, and the phylogenetic structures of both the ST and NT communities tended to be differentiated, with competitive exclusion being the main mechanism of plant assembly. However, shallow tillage increased the relative importance of the stochastic processes dominated by dispersal limitation, mitigating plant competition in the communities. This conclusion was supported by the Raup-Crick difference index-based analysis. Therefore, for the ecological restoration of the Mu Us Desert, species with adaptability and low niche overlap should be selected to increase the utilization efficiency of the environmental resources. The results of this study provide a foundation for policy development for ecosystem management and restoration in the Mu Us Desert.